PENGARUH KECERDASAN SPIRITUAL, KARAKTERISTIK INDIVIDU, DAN KECERDASAN EMOSIONAL TERHADAP KEEFEKTIFAN KEPEMIMPINAN KEPALA SMK NEGERI 1 PALU - Fatma, Fatma (Katalogis, 2015)
The objectives of this research are: first, to discover whether spiritual quotient, individual characteristics, and emotional quotient simulataneously and partially have effects on leadership effectiveness of the principal of SMK Negeri 1 Palu; second, to determine the variable that has dominant effect on leadreship effectiveness of the principal of SMK Negeri 1 Palu. The subject of this study consists 0f 53 teachers in SMK Negeri 1 Palu out of 72 teachers; 8 males teachers (15,1%) and 45 female teachers (84,9%). By using census sampel method, the data in this study is collected through questionnaires and observations and is analyzed bu using multiple linear regressions. The results show that simultaneously, spiritual quotient, individual characteristics, and emotional quotient significantly have effects on leadership effectiveness. Partial tests show that spiritual quotient, individual characterstics, and emotional quotient significantly affect the leadership effectiveness. The result also reveals that dependent variable that has dominant effect on the principal’s leadership effectiveness is spiritual quotient.